Evidence for the Innervation of Sperm-host Glands (SHG) of Native Chicken`s (Gallus domesticus) Oviduct - Das, S.K. (International Journal of Poultry Science, 2003)
The presence of neural tissues and smooth muscle elements in the vicinity of the oviductal sperm-host glands at uterovaginal junction of deshi chicken was demonstrated by medium (X40) and high (100X) light microscopy. Relevant samples were collected and passed through H and E stain in histology laboratory of the Department of Anatomy and Histology, BAU, Mymensingh, Bangladesh. Smaller and segregated nerve ganglions were observed in the submucosa and also in the lamina propria of the core of the villi by bright field microscopy. Smooth muscle fibers were also obvious in the surrounding areas. The evidence for the innervation of the sperm-host glands in chicken`s oviduct suggested that it might have a functional role in oviductal sperm storage in and release of spermatozoa from, the sperm-host glands of native hens.